Interplay between neutrophils and trophoblast cells conditions trophoblast function and triggers vascular transformation signals. Issue 4 (26th September 2019) - Calo, Guillermina; Sabbione, Florencia; Pascuali, Natalia; Keitelman, Irene; Vota, Daiana; Paparini, Daniel; Ramhorst, Rosanna; Parborell, Fernanda; Trevani, Analía; Leirós, Claudia Pérez
Abstract: Normal placentation entails highly regulated interactions of maternal leukocytes with vascular and trophoblast cells to favor vascular transformation. Neutrophil activation and neutrophil extracellular trap (NET) formation associate with poor placentation and severe pregnancy complications. To deepen into the mechanisms of trophoblast–neutrophil interaction, we explored the effects of NETs on trophoblast cell function and, conversely, whether trophoblast cell‐derived factors condition neutrophils to favor angiogenesis and anti‐inflammatory signals required for fetal growth. NETs isolated from activated neutrophils hindered trophoblast cell migration. Trophoblast conditioned media prevented the effect as well as the vasoactive intestinal peptide (VIP) known to regulate trophoblast and neutrophil function. On the other hand, factors released by trophoblast cells and VIP shaped neutrophils to a proangiogenic profile with increased vascular endothelial growth factor synthesis and increased capacity to promote vascular transformation. Results presented here provide novel clues to reconstruct the interaction of trophoblast cells and neutrophils in vivo during placentation in humans. Abstract : Activated neutrophils and neutrophil extracellular traps adversely affect trophoblast cell function and might alter vascular transformation processes required during placentation. Factors released by trophoblast cells and vasoactive intestinal peptide reverse these effects and stimulate angiogenic processes.